Conducting Arts-Based Research with Rural Women in Columbia, South America: A Tool for Community Empowerment and Gender Justice - Peñaloza-Farfán, Lady; Flores-Hinojos, Irma (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2024)
Women's social movements in Colombia are known for being visible in the streets, on social networks, in the courts, and neighborhoods (Zulver, 2022). In Colombia, women have mobilized to seek gender justice. Many of them have to face violence not only daily, but also in a structural way such as the legal impossibility of owning land. Sometimes, mobilizing means exposing themselves to the dynamics of power and violence to which they are subjected (Rojas, 2000). Many women, however, seek to form associations to protect themselves from these dynamics. Associating and organizing as a collective allows women to start transcending the patriarchal structures that keep them in a situation where they are held as immobilized victims, and in turn, become the new protagonists of a struggle that allows them to be the builders of a different destiny for themselves and future generations (Llevadot, 2022). This new scenario demands that women recognize the importance of building a collective identity that can lead them to establish common objectives that are broader compared to the individual goals that lead them to satisfy their immediate and daily needs. Building this identity implies establishing actions that commit them, through participation, to change how they interact with their closest people and the social and political environment in their territories (Zulver, 2022). Some of these actions are expressed in the production of handicrafts, food, embroidery, theatrical performances, and other community activities that strengthen the community's organization.